CONTEMPORARY PARADIGMS OF MANAGEMENT OF ORGANIZATIONAL SISTEMS - B. Stavrić (Journal of Engineering & Processing Management, 2009)
Unlike the classical management approach based on hierarchical relations within an organization, a behaviorist concept of business systems management attracts more and more light. This refers to new paradigms of management such as organizational behavior, as well as the culture and climate of an organization. Organizational behavior targets individuals, as well as working groups, all the way to the business system as a whole, while organizational culture is observed through moral, social and behavioral norms of an organization, based upon beliefs, attitudes and priorities of its members. Organizations wishing to be not only more effective, but also a more pleasant working environment, have to do some research into the behavior of its members. That enables the prevention of conflicts and productive channeling of human endeavors. Understanding of human behavior is necessary for improving the functioning and bringing the wishes and needs of an organization and its members closer. These approaches are usually followed by the phenomenon of organizational climate, which refers to the hallmarks of workplace environment and represents the accepted model for establishing an agreeable atmosphere within the organizational structure given. This is the way to advance relations that are being established within an organizational system in order to increase its business activities efficacy and humanize the work as well. It is necessary to add the emotional intelligence of the leaders to the concepts previously mentioned as yet another modern paradigm of organizational systems management.
Keywords: behaviorism; climate; culture; management; organization; behavior